WOMEN’S STRUGGLE IN WORLD WAR II AS DEPICTED INKRISTIN HANNAH’STHE NIGHTINGALE - LintangImanina, 121511223003 (2018)
This study is conducted to reveal the issue of French women's struggle in World War II depicted in the novel The Nightingale. Generally, the story with the theme of historical fiction portrays men as the main character. Those who serve as soldiers are considered important by the people because they have a purpose to defend the country. The war conditions require someone to have physical and mental strength, and also high intelligence in dealing with the enemy. However, the nature of women formed by the traditional gender roles such as weak and passive is on the contrary to the desired role, thus their participation in war is limited only as a nun or a cook. In this research, Isabelle and Vianne decided to fight in different ways. Isabelle joined the resistance group under the command of Charles de Gaulle, while her older sister made a tacit resistance in her home by rescuing half Parisian-Jewish children from an orphanage. The resistance that they built refers to the term frontline feminism where women are in a position that is essentially at risk and can endanger themselves. This research used feminism approach and frontline feminism as the concept theory. According to the concept of theory, their strategy was categorized as nonviolent action. The results of this study indicates that the struggle which is conducted by Isabelle and Vianne strive to achieve freedom in the middle of war by retaining their feminine side without changing into masculine.Itbecomes the main strategy against patriarchy nonviolent with nonviolent action.